Safety assessment of the process 'General Plastic', based on Starlinger Decon technology, used to recycle post‐consumer PET into food contact materials. (10th August 2018) - ,; Silano, Vittorio; Barat Baviera, José Manuel; Bolognesi, Claudia; Brüschweiler, Beat Johannes; Chesson, Andrew; Cocconcelli, Pier Sandro; Crebelli, Riccardo; Gott, David Michael; Grob, Konrad; Lampi, Evgenia; Mortensen, Alicja; et al.
Abstract: This scientific opinion of the EFSA Panel on Food Contact Materials, Enzymes, Flavourings and Processing Aids (CEF Panel) deals with the safety evaluation of the recycling process General Plastic (EU register No RECYC153), which is based on the Starlinger Decon technology. The decontamination efficiency of the process was demonstrated by a challenge test. The input of this process is hot caustic washed and dried poly(ethylene terephthalate) (PET) flakes originating from collected post‐consumer PET containers, mainly bottles, containing no more than 5% of PET from non‐food consumer applications. In this technology, washed and dried PET flakes are preheated before being submitted to solid‐state polycondensation (SSP) in a continuous reactor at high temperature under vacuum and gas flow. Having examined the challenge test provided, the Panel concluded that the preheating (step 2) and the decontamination in the continuous SSP reactor (step 3) are the critical steps that determine the decontamination efficiency of the process. The operating parameters that control the process performance are well defined and are temperature, pressure, residence time and gas flow for steps 2 and 3. Under these conditions, it was demonstrated that the recycling process under evaluation, using the Starlinger Decon technology, is able to ensure that the level of migration of potential unknown contaminants into food is below a conservatively modelled migration of 0.1 μg/kg food. Therefore, the Panel concluded that the recycled PET obtained from this process intended to be used up to 100% for the manufacture of materials and articles for contact with all types of foodstuffs for long‐term storage at room temperature, with or without hotfill, is not considered of safety concern. Trays made of this PET are not intended to be used, and should not be used, in microwave and conventional ovens.